2020
DOI: 10.1128/aac.00687-20
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Caspofungin among Extracorporeal Membrane Oxygenation Patients during the Postoperative Period of Lung Transplantation

Abstract: Background:Little is known about the influence of extracorporeal membrane oxygenation (ECMO) on the pharmacokinetics (PK) of caspofungin. The aim of this study was to describe population PK of caspofungin in patients with and without ECMO during the postoperative period of lung transplantation (LTx) and investigate covariates influencing caspofungin PK. Methods:We compared ECMO patients with non-ECMO patients, and patients before and after ECMO weaning as self-controls, to analyzed changes in caspofungin PK. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…We also examined ECMO as a covariate and found no significant effect of ECMO on the PK of caspofungin. The same conclusion was reached by a previous study ( 38 ) by Wang et al, who investigated the PK of caspofungin in lung transplant recipients on ECMO therapy. This is potentially attributable to the fact that the ECMO circuit may not sequester caspofungin in vivo .…”
Section: Discussionsupporting
confidence: 83%
“…We also examined ECMO as a covariate and found no significant effect of ECMO on the PK of caspofungin. The same conclusion was reached by a previous study ( 38 ) by Wang et al, who investigated the PK of caspofungin in lung transplant recipients on ECMO therapy. This is potentially attributable to the fact that the ECMO circuit may not sequester caspofungin in vivo .…”
Section: Discussionsupporting
confidence: 83%
“…A case report (22) observed that the standard dose of caspofungin failed to reach the target plasma concentration level during ECMO support. However, other in vivo studies (23)(24)(25) have suggested that ECMO does not affect the pharmacokinetic characteristics of caspofungin. Caspofungin is hydrophilic (log P −2.798) but has a high protein binding rate (97%), which may lead to significant differences in its recovery in different types of ECMO circuits.…”
Section: Discussionmentioning
confidence: 95%
“…Three studies enrolled a pediatric population between three months and 18 years, while the rest included adults only. Five studies focused on transplant patients, including allogeneic hematopoietic stem cell transplant [ 25 , 32 ], heart transplant [ 29 ], lung transplant [ 30 ], and liver transplant [ 26 ]. While most studies collected only plasma concentrations, Pressiat et al [ 26 ] collected plasma and peritoneal fluid samples.…”
Section: Resultsmentioning
confidence: 99%